Analysis of Health and Safety Risk Management (OHS) - Alfian Krisdarmanto; Diah Ayu Restuti Wulandari (NAROTAMA UNIVERSITY, Indonesia, 2022)
This study intends to identify OHS risks in the workforce, control risks, and assess risks that occur in construction projects. This implementation was carried out in the KPP Sidoarjo State House Rehabilitation project. This data collection uses the interview method and filling out questionnaires directly to the workforce as many as 15 respondents who then arrange the risk potential variables based on each job so that 37 potential risk variables are produced. In the conclusion, there are results of the risk level assessment based on the AS/NZS 4360 standard, there are 20 variables that are categorized as medium level and 17 variables that are categorized as low level. exposed to noise when using a grinding machine when cutting ceramics (ceramic installation process), while for the lowest value of 1.47 which is included in the low level, the workers' eyes are exposed to paint splashes (painting process).